Is There a Duty to Die? - Hardwig, John (The Hastings Center report, 1997)
Many people were outraged when Richard Lamm claimed that old people had a duty to die. Modern medicine and an individualistic culture have seduced many to feel that they have a right to health care and a right to live, despite the burdens and costs to our families and society. But in fact there are circumstances when we have a duty to die. As modern medicine continues to save more of us from acute illness, it also delivers more of us over to chronic illnesses, allowing us to survive far longer than we can take care of ourselves. It may be that our technological sophistication coupled with a commitment to our loved ones generates a fairly widespread duty to die.